Geospatial approach to study the food environment according to the DASH diet guidelines, an Argentinian experience - Campero, Micaela Natalia; Scavuzzo, Carlos Matías; Oberto, María Georgina; Marchiori, Georgina Noel; Popelka, Regina María; Defagó, María Daniela (Universidad y Salud, 2024)
Introduction: The characteristics of the food environment influence food choices. Objective: To design and implement a methodology to explore the characteristics of the food environment in a central neighborhood of Córdoba, Argentina, based on the availability of food stores and following the recommendations of the DASH diet (Dietary Approaches to Stop Hypertension). Materials and Methods: 223 stores were analyzed to determine the type of establishment and the availability of foods based on the mentioned approaches. They were georeferenced using coordinates extracted from the Google Earth platform. Then, stores were classified, constructing a continuous quantitative variable that summarizes information about product sales in each place (DASH score). The thematic mapping and score construction were carried out using QGIS 3.22 software. Results: A high predominance of kiosks, bakeries, and fast-food outlets (59.5%) was observed, while stores selling only fresh food represented 17.4% of the total. Additionally, establishments considered 'unhealthy' were mostly located in the northern part of the Alberdi neighborhood in Córdoba. Conclusions: The proposed approach contributes to the study of food environments as a tool for preventing non-communicable diseases and promoting health.